cmvIL-10 stimulates the invasive potential of MDA-MB-231 breast cancer cells. - Cendy A Valle Oseguera; Juliet V Spencer (PLoS ONE, 2014)
Cancer is the result of unregulated cell growth that leads to tumor formation, and in many cases, metastases. Although there are several risk factors associated with cancer, one area that remains poorly understood is the impact of infectious disease. Human cytomegalovirus (HCMV) is a member of the herpesvirus family that is highly prevalent in the population. HCMV usually causes clinical disease only in immune compromised individuals, but recent evidence suggests that HCMV may be strongly associated with some forms of cancer, particularly glioblastoma and breast cancer. We investigated the possibility that cmvIL-10, a viral cytokine with homology to human IL-10 that is secreted from infected cells, could act in a paracrine manner to alter the tumor microenvironment, induce cell signaling, and increase the invasive potential of cancer cells. We found that human MDA-MB-231 breast cancer cells express the IL-10 receptor and that exposure to cmvIL-10 results in activation of Stat3, a transcription factor strongly associated with enhanced metastatic potential and chemo-resistance. In addition, cmvIL-10 stimulated an increase in DNA synthesis and cell proliferation, protected MDA-MB-231 cells from etoposide-induced apoptosis, and also greatly enhanced chemotaxis toward epidermal growth factor (EGF). These results suggest a significant and wide-ranging role for cmvIL-10 in the progression of breast cancer and could have broad implications for the diagnosis and treatment of cancer in HCMV-positive patients.